Measuring the Voice Resemblance Extent of Identical (Monozygotic) Twins Using Voiceprints Neutrosophic Domain - Khaleel, Yazen A.; Daniel, Caroline Y.; Yahya, Salah I. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
The identical twins (Monozygotic) are siblings created from the division of one fertilized egg (zygote), so they will be identical in their genetic characteristics and therefore in their phenotypic traits to a very large extent. Among these traits is the voice or the voiceprint of these twins. This research aims to suggest a method to determine the extent of the similarity and the difference between the voiceprints between the brothers of the identical twins and thus, it is possible to distinguish between their voices. This study relied on using a number of audio clips collected from 35 identical twins. The proposed method is based on the use of the spectrogram that represents the voiceprint of the twins. The spectrogram is a two-dimensional function that can be used in the Neutrosophic Transformation to convert the voiceprints to the Neutrosophic domain represented by three membership functions (True, False, and Indeterminate). The results showed that the average extent of the similarity ratio between twins’ voices (True membership) is 67.6%, the difference ratio (False membership) is 32.3%, and the indeterminacy membership function ratio is 18.2%.